Influence of Aspect and Elevational Gradient on Vegetation Pattern, Tree Characteristics and Ecosystem Carbon Density in Northwestern Himalayas - D. R. Bhardwaj (MDPI AG, 2021)
Himalayan forest has been threatened by rapid anthropogenic activities, resulting in the loss of forest diversity and climate change. The present study was carried out on four aspects (northern, southern, western and eastern), at three different altitudinal ranges, namely, 1000–1300 m above sea level (m a.s.l.), 1300–1600 m a.s.l. and 1600–1900 m a.s.l., and at three diverse mountain ranges (Kalaghat, Barog and Nangali) of sub-temperate forest ecosystems of the mid Himalayan ranges, to elucidate their influence on vegetation, tree characteristics and ecosystem carbon density. The results revealed that Pinus roxburghii is the most dominant forest community of the mid Himalaya’s forest, irrespective of altitudinal gradient and slope. The south-facing slopes are occupied by the xerophytic tree species frequently found in the lower Shiwalik P. roxburghii forest, whereas the north-facing ones are dominated by mesophyllic species, such as Cedrus deodara and Quercus leucotrichophora, which commonly grows in the northwestern Himalayan temperate forest ecosystem. The maximum stem density (211.00 Nha−1) was found at 1000–1300 m a.s.l., and on the northern aspect (211.00 Nha−1). The maximum stem volume (236.50 m3 ha−1) was observed on the northern aspect at 1000–1300 m a.s.l., whereas the minimum (32.167 m3 ha−1) in the southern aspect at 1300–1600 m a.s.l. The maximum carbon density (149.90 Mg ha−1) was found on the northern aspect and declined with increasing elevation from 123.20 to 74.78 Mg ha−1. Overall, the study establishes that the southern and western aspects are very low in carbon density, whereas the northern aspect represents higher biodiversity as well as carbon and nutrient stocks. Therefore, aspect and altitude should be given due importance for efficient managing of biodiversity and mitigating climate change.